2021
DOI: 10.1172/jci.insight.149257
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal microbiota and metabolome predict preterm birth risk in an ethnically diverse cohort

Abstract: Integration of cervicovaginal microbiota, metabolome and host response data provide useful insight into preterm birth risk stratification in an ethnically diverse cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 69 publications
1
67
0
Order By: Relevance
“…17,18 Areas for further investigation include the use of progesterone in twin pregnancies with a short cervix, the role of the microbiome and inflammation in preterm birth in multiple pregnancy. 19 A key knowledge gap highlighted in the recent MBRRACE Special Report on perinatal mortality in twins is the best management of delivery of the second twin in a diamniotic pregnancy where the first twin has delivered spontaneously at an extremely preterm gestation and the second sac remains intact and there is no spontaneous labour or maternal compromise. 6 The report identified that in several cases the delivery of the second twin was augmented with no clear indication, despite a lack of consensus on management in this circumstance and the knowledge that an inter twin interval of days or weeks is possible in certain circumstances.…”
Section: Preterm Birthmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Areas for further investigation include the use of progesterone in twin pregnancies with a short cervix, the role of the microbiome and inflammation in preterm birth in multiple pregnancy. 19 A key knowledge gap highlighted in the recent MBRRACE Special Report on perinatal mortality in twins is the best management of delivery of the second twin in a diamniotic pregnancy where the first twin has delivered spontaneously at an extremely preterm gestation and the second sac remains intact and there is no spontaneous labour or maternal compromise. 6 The report identified that in several cases the delivery of the second twin was augmented with no clear indication, despite a lack of consensus on management in this circumstance and the knowledge that an inter twin interval of days or weeks is possible in certain circumstances.…”
Section: Preterm Birthmentioning
confidence: 99%
“…There is, however, now high‐quality evidence supporting the use of physician examination indicated cerclage in twin pregnancies 17,18 . Areas for further investigation include the use of progesterone in twin pregnancies with a short cervix, the role of the microbiome and inflammation in preterm birth in multiple pregnancy 19 . A key knowledge gap highlighted in the recent MBRRACE Special Report on perinatal mortality in twins is the best management of delivery of the second twin in a diamniotic pregnancy where the first twin has delivered spontaneously at an extremely preterm gestation and the second sac remains intact and there is no spontaneous labour or maternal compromise 6 .…”
Section: Preterm Birthmentioning
confidence: 99%
“…Vaginal microbiota composition is strongly influenced by genetic, environmental, individual and lifestyle factors [2]. Recent evidence supports that the composition of the cervicovaginal microbiota plays a role in pregnancy outcome and it can be linked to adverse obstetric outcomes such as preterm birth, a leading cause of neonatal morbidity and mortality worldwide [3,4]. Moreover the microorganisms residing within the female reproductive tract have been associated with Assisted Reproductive Technologies (ART) outcomes [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, screening for asymptomatic BV in pregnancy in low-risk groups has not aided preterm birth prediction, and evidence is insufficient or conflicting even in studies of higher-risk groups ( 4 ). Nevertheless, numerous studies have pursued the association between the vaginal microbiome and PTB risk ( 5 16 ), including our own ( 15 ), and many of the species identified as associated with higher risk of PTB overlap those associated with BV.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in microbiota composition are reflected in variations in bacterially derived metabolite profiles ( 11 , 15 , 17 ), which may have functional impact ( 18 21 ). Consistent with the microbiome studies, elevated vaginal lactate, which is the major product of the lactobacilli, and succinate have been found to be associated with term delivery ( 11 ), while elevated acetate was subsequently found to be higher in women who delivered preterm compared with term ( 17 ).…”
Section: Introductionmentioning
confidence: 99%